Hume on causation - Beebee, Helen 1968- (Routledge, 2006)
"Hume on Causation is the first major work dedicated to Hume's views on causation in over fifteen years. It places Hume's interest in causation within the context of his theory of the mind and his theory of causal reasoning, arguing that Hume's conception of causation derives from his conception of the nature of the inference from causes to effects. Helen Beebee argues that Hume's interest in inductive reasoning is an interest in the psychological process involved in inferring effects from causes, and not in the epistemological 'problem of induction' as traditionally conceived. She also motivates and develops a projectivist interpretation of Hume's theory of causation, according to which our causal talk is an expression of our inferential habits, and argues that for Hume the projection of those habits affects not only how we conceive of the world, but also how we see it."--BOOK JACKET.
Includes bibliographical references
Keywords: Hume, David -- 1711-1776; Causation; Kausalität